Emerging trends and research foci in autophagy of pancreatic cancer: a bibliometric and visualized study - Fan, Linlin; Wei, Zhiyong; Liu, Lili; Qi, Xiaojie; Yu, Hong (Frontiers in Oncology, 2023)
Objective: The purpose of this study was to analyze the trends by year, country, institution, journal, reference and keyword in publications on the autophagy of pancreatic cancer (PC) and to predict future research hotspots. Methods: The Web of Science Core Collection was used to search for publications. The contributions of various countries/regions, institutes, authors, identified research hotspots, and promising future trends were analyzed using the VOSviewer1.6.16 and CiteSpace6.6.R2 programs. We also summarized autophagy relevant clinical trials of PC. Results: A total of 1293 papers on the autophagy of PC published between 2013 and 2023 were included in the study. The average number of citations per article was 33.76. The China had the most publications, followed by USA, and a total of 50 influential articles were identified through co-citation analysis. Clustering analysis revealed clusters of keywords: metabolic reprogramming and ER stress, mTOR-mediated apoptosis, extracellular trap as the most concerned clusters. The co-occurrence cluster analysis showed pancreatic stellate cell, autophagy-dependent ferroptosis, autophagy-related pathway, metabolic rewiring, on-coding RNA as the highly concerned research topics in recently. Conclusion: The number of publications and research interest have generally increased over the past few years. The China and USA have made prominent contributions to the study of the autophagy of PC. The current research hotspots mainly focus not only on the related modulation, metabolic reprogramming, ferroptosis of tumor cells themselves, but also on tumor microenvironments such as autophagy associated pancreatic stellate cells and new treatments targeting autophagy.